Information security applications : 20th International Conference, WISA 2019, Jeju Island, South Korea, August 21-24, 2019, Revised selected papers /: 20th International Conference, WISA 2019, Jeju Island, South Korea, August 21-24, 2019, Revised selected papers. ([2020]) - Unknown
No abstract available